PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SD NEGERI 2 SIDOHARJO - Wulandari, Siti; Rijal, Akmal; Frima, Aren (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the achievement of IPAS learning outcomes among fourth-grade students at SD Negeri 2 Sidoharjo after the implementation of the Contextual Teaching and Learning (CTL) model. The research employed a quantitative method using a One-Group Pre-test and Post-test Design. The population consisted of all fourth-grade students at SD Negeri 2 Sidoharjo, with a sample of 26 students. Data were collected through tests. The research instrument was a multiple-choice test that had been tested for validity and reliability. Based on the hypothesis testing results, it was found that Z hitung ≥ Z tabel (5,00 ≥ 1,64), therefore, H₀ was rejected and Hₐ was accepted. In other words, the hypothesis proposed in this study was accepted, indicating that the learning outcomes of fourth-grade students in IPAS on Chapter 7, "How Do We Obtain All Our Needs?", Topic A, "Me and My Needs," at SD Negeri 2 Sidoharjo significantly achieved mastery after the implementation of the Contextual Teaching and Learning (CTL) model.